Surgical Intervention for Chronic Mesenteric Ischemia - Klein, Andrea; Bennett, Lisa; Ha, Cindy; Kirkwood, Melissa L. (Digestive Disease Interventions, 2018)
Symptomatic chronic mesenteric ischemia (CMI) is a relatively rare condition, yet there are significant clinical consequences for those affected by the disease. CMI not only reduces quality of life but also increases an individual's risk for life-threatening acute mesenteric ischemia. Surgery is the definitive treatment to reduce the risk for this potentially fatal outcome, and both endovascular and open surgical strategies are currently utilized. This review article discusses the approach to making a diagnosis of CMI, as well as the surgical techniques used to revascularize the mesenteric circulation.
Keywords: mesenteric ischemia; mesenteric bypass; mesenteric artery angioplasty and stenting